Reverse Determination of Face-milling Cutter Radius of Curvilinear Cylindrical Gears Using Contact Pattern - Zhang Xuegang; Dong Yingjie (Jixie chuandong)
To design a curvilinear cylindrical gear with arbitrary tooth surface contact pattern, a method for determining the radius of a disc-shaped milling cutter for machining the curvilinear cylindrical gear was proposed based on the reverse determination of the required dimensions of the contact pattern. Firstly, the mathematical model of the tooth surface of the curvilinear cylindrical gear was introduced. Secondly, a mathematical model for calculating the contact patterns was established. Then, taking four curvilinear cylindrical gears machined by double-edged milling cutters with different radii as examples, the relation graph between the radius of the disc-shaped milling cutter and the contact patterns was studied. Finally, the radius selection of the disc-shaped milling cutter was achieved through interpolation. This method can skip the gear trial processing, reduce the manufacturing cost of gears, and lay the foundation for the design and manufacturing of fixed-setting face-milling curvilinear cylindrical gears.